KARAKTERISTIK SEORANG PELAYAN TUHAN BERDASARKAN 1 TIMOTIUS 3:1-7 - Waharman Waharman (Manna Rafflesia, 2017)
God's servant is a noble status, the glory is not based on his position, material and wages. But the glory is found in the characteristics of His servants. It is the characteristic that maintains one's service and maintains its status of service as noble. But many cases show the difficulty of a service to maintain its characteristics. In Paul's letter to Timothy reminded him to be able to assign a servant with high value criteria. Therefore through this writing, I will give the principles and characteristics of a minister based on 1 Timothy 3: 1-7.